KARAKTERISASI SIFAT ELEKTROKIMIA ELEKTRODA KARBON AKTIF BERBASIS LIMBAH SABUT KELAPA MUDA MENGGUNAKAN SEPARATOR MEMBRAN KULIT TELUR AYAM - Angela Carolina Simanjuntak; Awitdrus Awitdrus (Komunikasi Fisika Indonesia, 2022)
The supercapacitor is an energy storage device with an electrochemical characteristic that can provide high energy and power density. The supercapacitor cell consists of a current collector, electrode, electrolyte, and separator. This study used young coconut fiber biomass as a supercapacitor electrode, H2SO4 as an electrolyte, 316L stainless steel as a current collector, and chicken eggshell membrane as a separator. The fabrication of electrode carbon made from young coco fiber begins with the pre-carbonization process, chemical activation using 0.5M KOH, carbonization process using N2 gas at a temperature of 600 °C, and physical activation using CO2 gas at a temperature of 750 °C. Analysis of electrochemical characteristics using cyclic voltammetry method resulting in a specific capacitance value of 197.05 F/g for a scan rate of 1 mV/s, 157.215 F/g for a scan rate of 2 mV/s, and 129.42 F/g for scan rate of 5 mV/s.